PENGARUH BERBAGAI BAHAN ORGANIK TERHADAP PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacaoL.) - Wan Lukman Nul Hakim; Zulfatri Zulfatri Zulfatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the effect of several organic materials and obtain good organic material for the growth of cocoa seedlings. The research was conducted at the Faculty of Agriculture University of Riau's experimental garden, starting from November 1, 2018 to February 28, 2019. This study used a completely randomized complete design (CRD) with 4 treatments and 5 replications so that it consisted of 20 experimental units. The parameters observed were seedling height, number of leaves, stem diameter, leaf area, root volume and root canopy ratio. The data were analyzed using variance and continued with a test of multiple levels of 5%. The administration of various organic ingredients did not significantly affect seedling height, number of leaves, stem diameter, root volume and root canopy ratio, but significantly different increased leaf area. Treatment without administration of organic ingredients can increase the leaf area of cocoa seedlings. Keywords : Cocoa, cocopeat, husk charcoal, Compost TKKS